Circulating Foamy Macrophages in the Golden Syrian Hamster (Mesocricetus auratus) Model of Leptospirosis. (November 2021) - Putz, Ellie J; Andreasen, Claire B; Stasko, Judith A; Fernandes, Luis G V; Palmer, Mitchell V; Rauh, Michael J; Nally, Jarlath E
Summary: Leptospirosis is a world-wide zoonotic disease caused by pathogenic Leptospira and can be asymptomatic or can cause clinical signs ranging from influenza-like to multi-organ failure and death in severe cases. While species and strain specificity can play a major role in disease presentation, the hamster is susceptible to most leptospiral infections and is the model of choice for vaccine efficacy testing. During evaluation of blood smears from hamsters challenged with different species and strains of Leptospira, a circulating population of large, mononuclear, lipid-filled cells, most similar to foamy macrophages (FMs), was detected. Circulating FMs were identified by Giemsa staining and verified by scanning and transmission electron microscopy. FMs were found in the circulating blood of all Leptospira -challenged hamsters, indicating that the finding was not species or strain specific, although higher numbers of FMs tended to correlate with severity of disease. The unique finding of circulating FMs in the hamster model of leptospirosis can yield additional insights into the pathogenesis of leptospirosis and other diseases that induce circulating FMs.